Job Opportunities, Amenities, and Variable Distance-Deterrence Elasticities: An Empirical Model of Inter-Municipal Migration in Belgium - Ludo Peeters (European Regional Science Association (ERSA), 2006)
This paper investigates inter-municipal migration flows in Belgium using a Poisson gravity model. Besides distance, the model also includes municipal-specific factors as explanatory variables. The model is tested using aggregate, cross-sectional, data on migrations between the municipalities of the Belgian province of Limburg, over the period 1998-2003. The model assumes heterogeneity of the distance-deterrence effect. The model also accounts for unobserved origin/destination characteristics. To overcome the problem of under-determinacy, we use the method of Generalized Cross-Entropy estimation. A number of major findings stand out. Firstly, we find evidence of a "U-shaped" relationship between the distance-deterrence elasticity and distance, where the distance elasticity is smaller for short-distance moves. Secondly, distance between origin and destination reinforces (attenuates) the pull effect of local employment opportunities (amenities). This finding may indicating a shift in the composition of migration flows from residential migration to labor migration as distance increases. Finally, the spatial distribution of the net pull effects of unobserved factors seem to coincide with proximity to major roads and railway stations.
Keywords: 330